The Drosophila RNA-binding protein HOW controls the stability of dgrasp mRNA in the follicular epithelium - Giuliani, Giuliano (Oxford University Press, 2014)
Post-transcriptional regulation of RNA stability and localization underlies a wide array of developmental processes, such as axon guidance and epithelial morphogenesis. In Drosophila, ectopic expression of the classically Golgi peripheral protein dGRASP at the plasma membrane is achieved through its mRNA targeting at key developmental time-points, in a process critical to follicular epithelium integrity. However, the trans-acting factors that tightly regulate the spatio-temporal dynamics of dgrasp are unknown. Using an in silico approach, we identified two putative HOW Response Elements (HRE1 and HRE2) within the dgrasp open reading frame for binding to Held Out Wings (HOW), a member of the Signal Transduction and Activation of RNA family of RNA-binding proteins. Using RNA immunoprecipitations, we confirmed this by showing that the short cytoplasmic isoform of HOW binds directly to dgrasp HRE1. Furthermore, HOW loss of function in vivo leads to a significant decrease in dgrasp mRNA levels. We demonstrate that HRE1 protects dgrasp mRNA from cytoplasmic degradation, but does not mediate its targeting. We propose that this binding event promotes the formation of ribonucleoprotein particles that ensure dgrasp stability during transport to the basal plasma membrane, thus enabling the local translation of dgrasp for its roles at non-Golgi locations.